Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1074/jbc.m109.057752
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Rad52 Amino-terminal DNA Binding Activity in DNA Strand Capture in Homologous Recombination

Abstract: Saccharomyces cerevisiae Rad52 protein promotes homologous recombination by nucleating the Rad51 recombinase onto replication protein A-coated single-stranded DNA strands and also by directly annealing such strands. We show that the purified rad52-R70A mutant protein, with a compromised aminoterminal DNA binding domain, is capable of Rad51 delivery to DNA but is deficient in DNA annealing. Results from chromatin immunoprecipitation experiments find that rad52-R70A associates with DNA double-strand breaks and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Expression and Purification of Recombinant Proteins-The following proteins were expressed and purified as described: Srs2 and Srs2-3KR (63), Aos1/Uba2, His-Ubc9, His-FLAGSmt3 (64), His-Siz1(1-465) (55), Mre11 (56), GST-Rad52 (57), and Rad59 (65).…”
Section: Methodsmentioning
confidence: 99%
“…Expression and Purification of Recombinant Proteins-The following proteins were expressed and purified as described: Srs2 and Srs2-3KR (63), Aos1/Uba2, His-Ubc9, His-FLAGSmt3 (64), His-Siz1(1-465) (55), Mre11 (56), GST-Rad52 (57), and Rad59 (65).…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we decided to construct an expression vector that expresses the Rad52-R70A mutant protein, which has a specific defect, i.e. impairment in annealing RPA-coated ssDNA, but is normal in recombination mediator and DNA binding activities (51). When the Rad52-R70A mutant protein was overexpressed in dna2-K1080E, it suppressed the lethality of dna2-K1080E poorly, as shown in Fig.…”
Section: Involvement Of Rad52 In Okazaki Fragment Processingmentioning
confidence: 99%
“…We were interested in the influence of Rad52 on RPAgoverned events such as DNA annealing. It was shown that RPA interferes with spontaneous annealing between two complementary ssDNA, which can be overcome by the addition of wild type Rad52 (44,51). To this end, we decided to construct an expression vector that expresses the Rad52-R70A mutant protein, which has a specific defect, i.e.…”
Section: Involvement Of Rad52 In Okazaki Fragment Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In canonical DSB repair, Rad52 has dual functions. In addition to its role as a recombination mediator for Rad51 recruit-ment, Rad52 also participates in ssDNA annealing, an activity critical for the capture of the second DNA end at the recombination site that generates Holliday junctions (16,17). Does HR, an almost universal DNA repair mechanism in all domains of life, also occur in mitochondria?…”
mentioning
confidence: 99%